Karakteristik Parkir di Rumah SakitKostati Surakarta - Suwardi, Suwardi (Jurnal Semesta Teknika, 2010)
Parking is very crucial, mainly in the city areas. It often disturbs the traffic. Nowadays, many hospitals provide insufficient parking areas. This research was carried out in the Kustati hospital, Surakarta. The aim of the research is to study the parking characteristic that is expected t o be useful in planning and managing the future parking in the Kustati hospital. The result showed that the existence of parking maneuver and the service degree of traffic in front of the Kustati hospital is ranging between C and D because of parking influenced to be D and E. The parking influenced maneuver towards the decrease of speed found out to be y = 31.3x + 14.22. The average parking accumulation of motor cycle maximum is 701. The average maximum of parking index is 123%. The majority of parking duration is 6 up to 7 hours (29 vehicles). The parking volume is about 1757 vehicles. Parking turn over is 3.1 vehicles . Therefore, it requires 198 m2 of additional parking area. The average of maximum of car parking accumulation is 84 cars. The maximum parking index is 105%. The majority of parking duration is 5 up to 6 hours (41 cars). The parking volume is 245 cars. Parking turn over is 3.1 cars.